Comparison of Induction of Labour with Sublingual Versus Vaginal Misoprostol 25 UG in a Primigravida with Post-Date Pregnancy: Sublingual vs Vaginal Misoprostol for Induction in Postdated Primigravida - Gul, Huma; Khattak, Sania Tanveer; Jan, Kaleemullah; Khan, Saima; Iqbal, Zahid; Sobia, .; Nazia, . (Pakistan Journal of Health Sciences, 2026)
In obstetrics, the induction of labour has been widely used in clinical practice for a decade. Misoprostol is effective for the induction of labour. It can be administered either sublingually or via the vaginal route. Objective: To compare the induction of labour with sublingual versus vaginal Misoprostol 25 ug in primigravida with postdate pregnancy. Methods: Our Study Prospective Comparative Study with consecutive sampling, conducted at the department of Gynecology, and Obstetrics at Saidu Group of Teaching Hospitals Swat, from March 2025 to September 2025 (6 months duration). Results: 160 participants were analyzed, with 80 in Group A (sublingual) and 80 in Group B per-vaginal route). Vaginal delivery within 24 hours occurred in 84.4% of the sublingual group and 80.8% of the vaginal group (p=0.612), while the mean induction-to-delivery time was significantly shorter in the sublingual group (9.1 ± 2.9 hrs vs. 10.4 ± 3.2 hrs; p=0.04). Maternal side effects and neonatal outcomes, including Apgar scores and birth weights, were comparable between the two groups. Conclusions: Both sublingual and vaginal misoprostol (25 µg) were effective for labour induction in post-date primigravida. The sublingual route demonstrated a significantly shorter induction-to-delivery interval with comparable safety outcomes, offering a practical alternative for routine clinical use.